With the Silent Glimmer of God’s Spirit: A Postmodern Look at the Sacraments - Karingen, Dipin Sebastian (Journal of Dharma, 2008)
Lambert J. Leijessen, With the Silent Glimmer of God’s Spirit: A Postmodern Look at the Sacraments, trans. Marie Baird with a foreword by George S. Worgul, New York: Paulist Press, 2006, pages: xii + 147, ISBN: 0-4437-9.